2014
DOI: 10.3892/or.2014.3495
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 8 involved in hypoxia promotes the invasion and metastasis of gastric cancer via epithelial to mesenchymal transition

Abstract: Abstract. Previously, we reported that hypoxia was able to induce invasion and metastasis in gastric cancer and that hypoxia-inducible factor-1 (HIF-1) is a key factor involved in this tumor type. Krüppel-like factor 8 (KLF8) as a transcriptional repressor has been suggested as a promoter of tumor metastasis in breast cancer and an inducer of the epithelial-mesenchymal transition (EMT). KLF8 is also highly expressed in gastric cancer tissues, contributing to poor prognosis. However, the association between KLF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
6
21
0
Order By: Relevance
“…In agreement with our finding, a number of previous studies have demonstrated that ectopic expression of KLF8 repressed E-cadherin expression, induced tumor cell EMT, and increased cell invasion and metastasis in breast cancer (6,22) and hepatocellular carcinoma (17). Furthermore, downregulation of KLF8 may inhibit cell invasion and metastasis in gastric cancer (23,24).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In agreement with our finding, a number of previous studies have demonstrated that ectopic expression of KLF8 repressed E-cadherin expression, induced tumor cell EMT, and increased cell invasion and metastasis in breast cancer (6,22) and hepatocellular carcinoma (17). Furthermore, downregulation of KLF8 may inhibit cell invasion and metastasis in gastric cancer (23,24).…”
Section: Discussionsupporting
confidence: 81%
“…An increasing number of transcription factors have been implicated in the repression of E-cadherin expression, including KLF transcription factor family proteins (6,23). KLF8 is a relatively new member of this family and is emerging as a crucial regulator of cancer initiation and progression (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KLF17 enhances Twist expression and consequently triggers EMT in endometrial cancer 27. KLF8 promotes the migration and invasion of gastric cancer cells by triggering EMT under hypoxic conditions 28. In our study, KLF6 inhibited the expression of mesenchymal markers, such as snail, slug, and vimentin.…”
Section: Discussionsupporting
confidence: 49%
“…2), a dual transcription factor implicated in cancer of many types 29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] that promotes the expression of EPSTI1 by transcriptional activation of the gene promoter. 23 Notably, KLF8 has been demonstrated to potently induce EMT by repressing E-cadherin 45 and cancer stem cell traits.…”
Section: Introductionmentioning
confidence: 99%